2021
DOI: 10.3390/ijms22073612
|View full text |Cite
|
Sign up to set email alerts
|

The Main Alkaloids in Uncaria rhynchophylla and Their Anti-Alzheimer’s Disease Mechanism Determined by a Network Pharmacology Approach

Abstract: Alzheimer’s disease (AD) is a growing concern in modern society, and effective drugs for its treatment are lacking. Uncaria rhynchophylla (UR) and its main alkaloids have been studied to treat neurodegenerative diseases such as AD. This study aimed to uncover the key components and mechanism of the anti-AD effect of UR alkaloids through a network pharmacology approach. The analysis identified 10 alkaloids from UR based on HPLC that corresponded to 90 anti-AD targets. A potential alkaloid target-AD target netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 56 publications
(31 reference statements)
1
28
0
Order By: Relevance
“…Rhy rescued hippocampal synaptic dysfunction in AD and acts as an inhibitor of ephrin type A-receptor 4-precursor (EphA4) tyrosine kinase [ 68 ]. Oral administration of Rhy reduced EphA4 activity in APP/PS1 transgenic mice as well as restored impaired recurrent potentiation in the hippocampus, substantiating the beneficial effects of Rhy on synaptic dysfunction in AD [ 69 ]. Although Rhy is very effective in reducing the pathogenesis of AD, it has certain limitations such as reduced solubility and poor bioavailability in brain tissue, and low permeability across the blood–brain barrier [ 70 , 71 ].…”
Section: Rhynchophylline and Nervous Disordersmentioning
confidence: 86%
“…Rhy rescued hippocampal synaptic dysfunction in AD and acts as an inhibitor of ephrin type A-receptor 4-precursor (EphA4) tyrosine kinase [ 68 ]. Oral administration of Rhy reduced EphA4 activity in APP/PS1 transgenic mice as well as restored impaired recurrent potentiation in the hippocampus, substantiating the beneficial effects of Rhy on synaptic dysfunction in AD [ 69 ]. Although Rhy is very effective in reducing the pathogenesis of AD, it has certain limitations such as reduced solubility and poor bioavailability in brain tissue, and low permeability across the blood–brain barrier [ 70 , 71 ].…”
Section: Rhynchophylline and Nervous Disordersmentioning
confidence: 86%
“…# p < 0.05 and ## p < 0.01 compared with the sham control group. *p < 0.05 and **p < 0.01 compared with the STZ control group chemical components for the treatment of AD [32][33][34]. Among these alkaloids, rhynchophylline (RN), isorhynchophylline (IRN), corynoxeine (CX), and isocorynoxeine (ICX) have been extensively studied, while other alkaloids derived from these Uncaria species have not been systematically studied yet [27,35].…”
Section: Discussionmentioning
confidence: 99%
“…RN was also found to improve the Aβ 1-42 -induced spatial cognitive impairments in rats [38] and suppress the Aβ-induced enhancement of spontaneous discharges in the hippocampal CA1 region of rats [39], suggesting that RN has neuroprotective effects on AD. It has been reported that 5 alkaloids in U. rhynchophylla including IRN and ICX are likely to be vital components for AD treatment in a potential alkaloid target-AD target network using a network pharmacology approach [33]. RN, IRN CX, and ICX are representative indole alkaloids from U. rhynchophylla and U. tomentosa.…”
Section: Discussionmentioning
confidence: 99%
“…Only GO terms in the category biological process were considered in this study. Top 20 GO biological processes and KEGG pathways sorted by the p value were visualized using an online tool ( http://www.bioinformatics.com.cn/ ) ( Zeng et al, 2021c ). We used the pathview software Microsoft Office Powerpoint (version 2019, Microsoft, Seattle, WA) to superimpose the UR targets involved in the Alzheimer disease pathway (hsa05010) and corresponding alkaloids on KEGG pathway map.…”
Section: Methodsmentioning
confidence: 99%